2021
DOI: 10.47489/p000s351z7821-6mc
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Aloe vera and Diclofenac on Body Weight, Blood Pressure and Renal Function of Hypertensive Rats

Abstract: Introduction: NSAIDs are known to cause salt and water retention leading to hypertension and renal impairment. Aloe vera gel has been used in medicinal preparations for decades. Limited data is available regarding effect of Aloe vera on renal function. There is a need to search this aspect of Aloe vera, to use it judiciously. Aims & Objectives: To estimate and compare the effects of Aloe vera and diclofenac on systolic blood pressure and renal functions of hypertensive rats. Place and duration of study: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Yaqoob et al investigated the effect of Aloe vera on blood pressure versus mono-dose diclofenac, administered daily, using a hypertensive experimental rat model. The study concluded that Aloe vera did not have a significant influence on blood pressure, while diclofenac led to increased values in the examined animals [ 43 ]. The available human studies on the blood pressure-lowering effect of Aloe vera are limited.…”
Section: Resultsmentioning
confidence: 99%
“…Yaqoob et al investigated the effect of Aloe vera on blood pressure versus mono-dose diclofenac, administered daily, using a hypertensive experimental rat model. The study concluded that Aloe vera did not have a significant influence on blood pressure, while diclofenac led to increased values in the examined animals [ 43 ]. The available human studies on the blood pressure-lowering effect of Aloe vera are limited.…”
Section: Resultsmentioning
confidence: 99%
“…A light and dark cycle of 12 hours was followed, and animals were given free access to food and water. Rats in Group A were given normal rat chow throughout the study period, whereas all the other groups were given normal rat chow containing sucrose (20% w/w)to induce hypertension, 8 which was induced in all three groups in eight weeks. Systolic blood pressure ≥ 140 mm Hg was considered hypertension 9 .…”
Section: A T E R I a L A N D M E T H O D Smentioning
confidence: 99%
“…The body weight and blood pressure of animals were recorded at baseline and then weekly throughout the study. Systolic blood pressure was measured by tail-cuff, 8 using a non-invasive blood pressure controller (ML125R) attached to the computer-based data recording system (Power lab). Twenty-four-hour urine was collected in a glass container by keeping each animal in a separate cage at 0, 8, and 10 weeks.…”
Section: A T E R I a L A N D M E T H O D Smentioning
confidence: 99%